The Use of Alternative DisputeResolution on the Supply of Medicines by the Brazilian Public Administration - Raquel Nery Cardozo; Jose Carlos Cardozo (Revista de Formas Consensuais de Solução de Conflitos, 2016)
This study aims to demonstrate the importance of using alternative resolution of healthrelated conflicts means involving the public administration in connection with the conflict between reserve against possible and the minimum existential theory, and "Structural Crisis of the Judiciary" driven legalization excessive conflict. It also contributes to the study of measures to ensure access to public health without the claimants have to submit to delay the trials, further contributing to improve the provision of judicial protection.